Necrotizing Sialometaplasia of the Hard Palate in a Patient Treated with Topical Nonsteroidal Anti-Inflammatory Drug - Alessandro Gatti; Emanuele Broccardo; Giuseppe Poglio; Arnaldo Benech (Case Reports in Dentistry)
Necrotizing sialometaplasia is a rare, benign, self-limiting, necrotizing process involving the minor salivary glands, mainly the mucoserous glands of the hard palate. It is thought to be the result of an ischemic event of the vasculature supplying the salivary gland lobules. Some predisposing factors such as smoking, use of alcohol, denture wearing, recent surgery, traumatic injuries, respiratory infections, systemic diseases bulimia, and anorexia have been described. Herein we present a case of necrotizing sialometaplasia of the hard palate in a patient without known predisposing factors, in our opinion, resulting from the use of topical anti-inflammatory drug. After diagnosis, the patient underwent treatment with chlorhexidine gluconate and a full palatal acrylic guard to protect the exposed bone from food residues during meals. After the sixth week the lesion regressed.